2020
DOI: 10.1101/2020.03.10.985507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observation of the Transport and Removal of Lipofuscin from the Mouse Myocardium using Transmission Electron Microscope

Abstract: This study was performed to investigate whether the lipofuscin formed within cardiomyocytes can be excluded by the myocardial tissue. We have provided indicators that can be used for future studies on anti-aging interventions.In the present study, the heart of a 5-month-old BALB/c mouse was obtained for resin embedding and ultra-thin sectioning. The specimens were observed under a Hitach 7500 transmission electron microscope, and the images were acquired using an XR401 side-insertion device.Lipofuscin granules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Extraneuronal lipofuscin was found in the brain samples, suggesting a possible physiological removal from the nerve cells to the capillary endothelium and its later elimination via phagocytosis by glia cells [ 127 ]. Indeed, recent findings have shown that lipofuscin could be exocytosed from the cardiomyocytes into circulation through capillary endothelium [ 128 ]. Hence, lipofuscin could be regarded as a promising redox biomarker of obesity and diabetes.…”
Section: Lipofuscin As a Novel Redox Biomarker Of Insulin-related Metabolic Diseasesmentioning
confidence: 99%
“…Extraneuronal lipofuscin was found in the brain samples, suggesting a possible physiological removal from the nerve cells to the capillary endothelium and its later elimination via phagocytosis by glia cells [ 127 ]. Indeed, recent findings have shown that lipofuscin could be exocytosed from the cardiomyocytes into circulation through capillary endothelium [ 128 ]. Hence, lipofuscin could be regarded as a promising redox biomarker of obesity and diabetes.…”
Section: Lipofuscin As a Novel Redox Biomarker Of Insulin-related Metabolic Diseasesmentioning
confidence: 99%
“…It has been also documented on rats that zinc deficiency promoted an accumulation of waste-trash products retinal pigment epithelium (RPE), concomitantly with lipofuscin-loaded macrophages in the choroids followed by the presence of such cells at Bruch’s membrane [ 16 ]. While Julien revealed that a zinc-based diet could exert beneficial effects on adult Long Evans (LE) rats, it was demonstrated this year, by Wang et al [ 17 ], through transmission electron microscope, that myocardial tissues of mice possess the ability to eliminate unnecessary bio-products into the associated bloodstream.…”
Section: Does Lipofuscin Really Possess a Branched Antagonistic Acmentioning
confidence: 99%